Enfrentamiento a una masa cervical no tiroidea en Atención Primaria - González A., Tomás; Fuenzalida M., Lucas; Gac E., Patricio; Rodríguez M., Francisco; Cabane T., Patricio; Rappoport W., Daniel (Revista Hospital Clínico Universidad de Chile, 2020)
The clinical approach to non-thyroid cervical masses in primary care has always been considered a diagnostic challenge. In the absence of specific diagnostic methods, the general practitioner must rely on clinic and general tests in order to achieve a suspected diagnosis and timely referral. On initial approach to cervical masses, one must first analyze each case according to patient age, associating an exhaustive anamnesis focused on the growth pattern and aggregate symptoms, along with a physical examination focused on signs of malignancy. Once completed, the etiology of the mass can be classified as probable congenital, inflammatory or tumoral origin. And also try to determine localization, temporality and discriminate between benign and malignant causes. Once the clinical interrogation has been completed, basic complementary tests and/or directed test according to suspicion can be requested. The foregoing allows the primary care physician a proper referral to specialist and/or initiation of appropriate treatment.